The study of morphology and electrochemical properties of supercapacitor working electrode based on multi-walled carbon nanotubes doped with nitrogen - P. M. Korusenko (Омский научный вестник)
In this work, we study the morphology, structure, specific surface area, conductivity, and electrochemical properties of the supercapacitor working electrodes prepared based on undoped and nitrogen-doped multi-walled carbon nanotubes (MWCNTs). It is shown that nitrogen-doped MWCNTs have a larger specific surface area and conductivity than MWCNTs due to the presence of structural defects and functional groups on their surface. Using scanning electron microscopy, it is shown that the electrodes formed based on undoped and nitrogen-doped MWCNTs have a porous structure, which ensures the penetration of electrolyte into the volume of the electrodes. A comparative analysis of the electrochemical characteristics of the supercapacitor electrodes in a unipolar acid electrolyte H2SO4 is carried out. Using cyclic voltammetry, it is shown that the high specific capacitance of the electrode based on nitrogen-doped MWCNTs at low scan rates is due to the additional contribution of Faraday processes involving structural defects, functional oxygen-containing and nitrogencontaining groups on the surface of nanotubes.